Answer:
(f-g)(x) = x^4 - x^3 - 4x^2 - 3
Step-by-step explanation:
(f-g)(x) = x^4 - x^2 + 9 - (x^3 + 3x^2 + 12)
(f-g)(x) = x^4 - x^2 + 9 - x^3 - 3x^2 - 12
(f-g)(x) = x^4 - x^3 - 4x^2 - 3
Answer:
10,471.2042
Step-by-step explanation:
Tbh Im not too sure
Answer:
1. -5
2. 0
Step-by-step explanation:
<em>1.</em> Distribute the Negative Sign:
=a−2a+−1(3a−(4a−5))
=a+−2a+−1(3a)+−1(−4a)+(−1)(5)
=a+−2a+−3a+4a+−5
Combine Like Terms:
=a+−2a+−3a+4a+−5
=(a+−2a+−3a+4a)+(−5)
Answer:
=−5
<em>2. </em>Distribute:
=(13)(5)+(13)(−t)+−5+t+(−12)(5)+(−12)(−t)
=65+−13t+−5+t+−60+12t
Combine Like Terms:
=65+−13t+−5+t+−60+12t
=(−13t+t+12t)+(65+−5+−60)
Answer:
=0
Answer:
schläfli symbol {50}, t{25}
Coxeter diagram
Symmetry group Dihedral (D50), order 2×50
Internal angle (degrees) 172.8°
5 more rows
Step-by-step explanation: